2000
DOI: 10.2169/internalmedicine.39.1054
|View full text |Cite
|
Sign up to set email alerts
|

Multiseptate Gallbladder with Cholelithiasis Diagnosed Incidentally in an Elderly Patient.

Abstract: A 70-year-old womanwith rheumatoid arthritis was admitted to our hospital because of gastric ulcers. Abdominal echography incidentally revealed that the patient' s gallbladder was multiseptate, an extremely rare anomaly. The diagnosis was confirmed by endoscopic retrograde cholangiography. This is the 26th case of multiseptate gallbladder in the world literature, but the patient is the oldest yet recorded with this condition. Furthermore, unlike most patients with multiseptate gallbladder, she had no biliary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 16 publications
0
10
0
3
Order By: Relevance
“…It has been postulated that the symptoms accompanying MSG can be the result of either stasis of the thickened bile that prevents normal emptying or uncoordinated contractions of the gallbladder that raise intraluminal pressure (Rivera-Troche and Hartwing 2009). Cholecystotomy is the choice of treatment in symptomatic patients (Miwa and others 2000, Karaca and others 2011). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been postulated that the symptoms accompanying MSG can be the result of either stasis of the thickened bile that prevents normal emptying or uncoordinated contractions of the gallbladder that raise intraluminal pressure (Rivera-Troche and Hartwing 2009). Cholecystotomy is the choice of treatment in symptomatic patients (Miwa and others 2000, Karaca and others 2011). …”
Section: Discussionmentioning
confidence: 99%
“…In this context, the abnormal condition of the gallbladder appears to be unrelated with the cause of death and is considered an incidental finding in this animal. Indeed, in human patients, MSG causes mainly abdominal pain and discomfort; moreover, clinical signs of abdominal pain can occur late in life in patients that have been otherwise healthy (Miwa and others 2000). …”
Section: Discussionmentioning
confidence: 99%
“…Эта опасность особенно велика у лиц, получающих имму-носупрессивную терапию. В мировой медицинской лите-ратуре имеются описания тяжелых деструктивных форм холецистита, развивающегося у больных РА [21][22][23]. При этом хорошо известно, что инфекционные осложне-ния являются одной из наиболее частых причин гибели па-циентов с этим заболеванием.…”
unclassified
“…In this abnormality, gallbladder is divided into compartments at different sizes by thin septa (Ozgen et al 1999;Miwa et al 2000). Although there are many reviews in the literature about MSG, ultrasonographic findings of MSG have not been reported.…”
mentioning
confidence: 99%